HDL-C concentration is related to markers of absorption and of cholesterol synthesis: Study in subjects with low vs. high HDL-C - Nunes, V.S.; Leança, C.C.; Panzoldo, N.B.; Parra, E.; Cazita, P.M.; Nakandakare, E.R.; de Faria, E.C.; Quintão, E.C.R. (Clinica chimica acta, 2011)
The antiatherogenic functions of high density lipoprotein (HDL-C) include its role in reverse cholesterol transport, but to what extent the concentration of HDL-C interferes with the whole-body cholesterol metabolism is unknown. Therefore, we measured markers of body cholesterol synthesis (desmosterol and lathosterol) and of intestinal cholesterol absorption (campesterol and β-sitosterol) in healthy subjects that differ according to their plasma HDL-C concentrations. Healthy participants presented either low HDL-C (< 40 mg/dl, n = 33, 17 male and 16 female) or high HDL-C (> 60 mg/dl, n = 33, 17 male and 16 female), BMI < 30 kg/m 2, were paired according to age and gender, without secondary factors that might interfere with their plasma lipid concentrations. Plasma concentrations of non-cholesterol sterols were measured by the combined GC–MS analysis. Plasma desmosterol did not differ between the two groups; however, as compared with the high HDL-C participants, the low HDL-C participants presented higher concentration of lathosterol and lower concentration of the intestinal cholesterol absorption markers campesterol and β-sitosterol. Plasma concentrations of HDL, and not the activities of LCAT and CETP that regulate the reverse cholesterol transport system, correlate with plasma sterol markers of intestinal cholesterol absorption directly, and of cholesterol synthesis reciprocally.